Inhibitory effects of selected cannabinoids against dipeptidyl peptidase IV, an enzyme linked to type 2 diabetes - Lithalethu Mkabayi; Zenobia Viljoen; Rui W.M. Krause; Kevin A. Lobb; Brett I. Pletschke; Carminita L. Frost (Heliyon, 2024)
Ethnopharmacological relevance: In recent times the decriminalisation of cannabis globally has increased its use as an alternative medication. Where it has been used in modern medicinal practises since the 1800s, there is limited scientific investigation to understand the biological activities of this plant. Aim of the study: Dipeptidyl peptidase IV (DPP-IV) plays a key role in regulating glucose homeostasis, and inhibition of this enzyme has been used as a therapeutic approach to treat type 2 diabetes. However, some of the synthetic inhibitors for this enzyme available on the market may cause undesirable side effects. Therefore, it is important to identify new inhibitors of DPP-IV and to understand their interaction with this enzyme. Methods: In this study, four cannabinoids (cannabidiol, cannabigerol, cannabinol and Δ9-tetrahydrocannabinol) were evaluated for their inhibitory effects against recombinant human DPP-IV and their potential inhibition mechanism was explored using both in vitro and in silico approaches. Results: All four cannabinoids resulted in a dose-dependent response with IC50 values of between 4.0 and 6.9 μg/mL. Kinetic analysis revealed a mixed mode of inhibition. CD spectra indicated that binding of cannabinoids results in structural and conformational changes in the secondary structure of the enzyme. These findings were supported by molecular docking studies which revealed best docking scores at both active and allosteric sites for all tested inhibitors. Furthermore, molecular dynamics simulations showed that cannabinoids formed a stable complex with DPP-IV protein via hydrogen bonds at an allosteric site, suggesting that cannabinoids act by either inducing conformational changes or blocking the active site of the enzyme. Conclusion: These results demonstrated that cannabinoids may modulate DPP-IV activity and thereby potentially assist in improving glycaemic regulation in type 2 diabetes.